Administrative cases: an effective alternative to lawsuits in assuring access to medicines? - Virginia Oliveira Chagas; Mércia Pandolfo Provin; Rita Goreti Amaral (BMC, 2019)
Abstract Background Although public policy in Brazil supports access to essential medicines, the health system cannot meet all demand. Increasingly, the population has used legal demands to seek access to medicines, an approach that can undermine equitable access by creating policy inconsistencies (e.g., granting access to medicines outside the SUS formulary). In response, the Executive Branch has signed institutional agreements to create an administrative case for submitting requests for medicines directly to the Executive Branch. The objective of this study was to assess the degree to which the administrative cases for requests are in accordance with public policies and guidelines, e.g., if administrative cases results in fewer decisions to purchase outside the SUS formulary. Methods This descriptive study used secondary data from lawsuits filed against the Executive Branch from 2003 to 2015 and from administrative cases granted by the Executive Branch from 2010 to 2015 in the capital of a state located in the central-western region of Brazil. The variables included plaintiffs' sociodemographic characteristics and diseases as well as the characteristics of the medical products sought via the processes. Results Comparing the requests submitted through lawsuits and the administrative cases revealed differences in the incomes of plaintiffs and the costs of medicines. Both methods for submission recorded requests for medicines for diseases of endocrine and circulatory systems; the only difference was the prevalence of diseases of the genitourinary system in the lawsuits. A higher proportion of lawsuits sought medicines outside the SUS formulary with therapeutic alternatives, while medicines outside the SUS formulary without an alternative were more commonly requested in administrative cases. Conclusion Administrative cases adhere to the public policies and guidelines of the SUS. The administrative cases results in fewer decisions to purchase outside the SUS formulary with alternative, and more decisions to purchase drugs for which there is a formulary alternative. In addition, administrative cases provide greater equity by favoring lower income applicants. However, administrative cases also reveal deficiencies in the State's implementation of existing pharmaceutical policies. The public pressure for effective implementation of existing policies may help expand access to medicines.